Effects of replacing Brachiaria hay with either Desmodium intortum or dairy concentrate on animal performance and enteric methane emissions of low-yielding dairy cows - Korir, Daniel; Eckard, Richard; Goopy, John P.; Arndt, Claudia; Merbold, Lutz; Marquardt, Svenja (Frontiers Media, 2022)
In Africa, cattle are often fed low quality tropical roughages resulting in low-yielding animals with high methane (CH4) emission intensity (EI, g CH4/per unit of product). Supplementation with protein is known to improve the nutritive value of the otherwise low-quality diets. However, animal nutrition studies in East Africa that are accompanied by CH4 emission measurements are lacking. Thus, an animal experiment was conducted to quantify the effect of supplementing cattle fed mainly on low-quality Urochloa brizantha hay (control diet; CON; crude protein (CP) = 7.4%) or supplemented with either a tannin-rich leguminous fodder, Desmodium intortum hay (DES) or a commercial dairy concentrate (CUBES) on voluntary dry matter intake (DMI), nutrient apparent total tract digestibility, nitrogen (N) retention, enteric CH4 production and animal performance (milk and average daily gain). Twelve mid-lactating crossbred (Friesian × Boran) cows (initial liveweight = 335 kg) were used in a 3×3 (Period × Diet) Latin square design with each period running for four weeks. Compared to CON, DES decreased nutrient (DM, OM, CP) intake, apparent total tract digestibility and daily milk yield. In contrast, CUBES increased nutrient intake and animal performance compared to CON, while nutrients’ apparent total tract digestibility was not different, except for CP digestibility that increased. Compared to CON, DES and CUBES improved overall N retention by the animals as a proportion of N intake. The DES diet compared with CON and CUBES, shifted the proportion of N excretion via urine to the fecal route, likely because of its tannin content. Both DES and CUBES, compared to CON, reduced methane yield (MY, g CH4/kg DMI) by 15% and 9%, respectively. The DES diet reduced absolute enteric CH4 emissions by 26% while CUBES increased emissions by 11% compared to CON. Based on the present findings, high supplementation levels (>50%) of Desmodium intortum hay is not recommended especially when the basal diet is low in CP content. Supplementation with lower levels of better managed Desmodium intortum forage however, need to be investigated to establish optimal inclusion levels that will improve animal productivity and reduce environmental impact of livestock in smallholder tropical contexts.